User Satisfaction Analysis On Gojek Application Services Using The Delone – Mclean Method Approach - Azizah, Hidayatul Putri; Veri, Jhon (Riset Sinergi Indonesia, 2025)
This study addresses key issues regarding the use of the Gojek application as a transportation tool, focusing on user satisfaction. The research employs the DeLone-McLean model to analyze factors influencing user satisfaction, including system quality, information quality, usability, user satisfaction, user intention, and business outcomes. In the context of increasing competition among online transportation services in Indonesia, understanding user satisfaction is crucial for the success and adoption of technology. Data were collected through a questionnaire distributed to 66 respondents at Universitas Tidar, focusing on their experiences with the Gojek application. The findings indicate that the Gojek application significantly impacts daily life and meets users' needs effectively, although some issues such as application errors were noted. Recommendations for improving service quality and adapting to technological advancements are discussed.